Sonography and sonoelastography in the detection of malignancy in superficial lymph nodes of dogs - Belotta, Alexandra F. [UNESP]; Gomes, Marcela C. [UNESP]; Rocha, Noeme S. [UNESP]; Melchert, Alessandra [UNESP]; Giuffrida, Rogerio; Silva, Jeana P. [UNESP]; Mamprim, Maria J. [UNESP] (Wiley-Blackwell, 2019)
Background The clinical applicability of sonography and sonoelastography (SOE) in the detection of lymph node malignancy in dogs has not been established. Objectives To compare sonographic and sonoelastographic findings between malignant and benign superficial lymph nodes and to evaluate the diagnostic performance of those methods. Animals One-hundred sixteen lymph nodes of 54 dogs. Methods A prospective observational study was used to investigate sonographic features and elasticity scores of malignant and benign superficial lymph nodes. Lymph nodes were categorized as malignant or benign according to cytology or histopathology. Quantitative variables were compared using Student's unpaired t test. Prevalence of categorical variables was compared using nonparametric Mann-Whitney U test. Diagnostic performance was calculated by receiver-operating characteristic analysis. Results Forty-nine malignant and 67 benign lymph nodes were included. Malignant nodes had larger long axis (LA; P = .0002), short axis (SA; P < .0001) and short-to-long axis ratio (P < .0001) in comparison with benign nodes. Malignant nodes had a higher prevalence of mixed vascular distribution on Doppler color flow mapping (P < .005) and on power Doppler (P < .0001) and higher resistivity index (RI; P < .0001), pulsatility index (P < .0001), and elasticity score (P < .0001) in comparison with benign nodes. Short axis, elasticity score, and RI offered the best accuracies, 80.2%, 78.1%, and 77.7% (P < .05), respectively, for malignancy detection. Conclusions and Clinical Importance Results support the use of Doppler sonography and SOE as auxiliary methods to brightness mode sonography to detect nodal malignancy.
Keywords: canine; Doppler; elastography; lymphoid tissue; ultrasound